Cultivation of seaweed Caulerpa racemosa on a laboratory scale using liquid organic fertilizer - Pramita, Susi; Erniati, Erniati; Zulpikar, Zulpikar; Khalil, Munawwar; Muliani, Muliani (Acta Aquatica: Aquatic Sciences Journal, 2022)
Indonesia is a maritime country that has seaweed natural resources that have the potential to be developed. Several types of seaweed have started to be cultivated by manipulating the cultivation environment such as providing various types of fertilizers to complement nutrient needs. This research was carried out at the Hatchery Laboratory of the Aquaculture Study Program, Faculty of Agriculture, Malikussaleh University in February -March 2020 which aims to determine the growth rate of Caulerpa racemosa by applying liquid organic fertilizer with different concentrations in the cultivation media. The design used was a non-factorial Completely Randomized Design (CRD) with 4 treatments and 3 replications, namely A Control (without giving liquid organic fertilizer), B (giving liquid organic fertilizer with a concentration of 0.22 mL fertilizer/L water), C (giving organic fertilizer). liquid concentration of 0.28 mL of fertilizer/L of water) and D (giving of liquid organic fertilizer with a concentration of 0.34 mL of fertilizer/L of water). The results showed that the application of liquid organic fertilizer had a very significant effect on the length growth rate of seaweed (Caulerpa racemosa). The best growth rate was in treatment D with a length growth rate of 9.2 cm. There was no significant difference between the weight growth rate and the regeneration rate of the thallus. However, based on the growth yield data for all treatments, it can be said that the higher the concentration of liquid fertilizer used, the better the growth of seaweed (Caulerpa racemosa).Keywords: Caulerpa rasemosa; Pertumbuhan; Pupuk cair; Rumput Laut.